Magnetocaloric Effect, Magnetoresistance of Sc0.28Ti0.72Fe2, and Phase Diagrams of Sc0.28Ti0.72Fe2−xTx Alloys with T = Mn or Co - Liting Sun; Hargen Yibole; Ojiyed Tegus; Francois Guillou (Crystals, 2020)
(Sc,Ti)Fe2 Laves phases present a relatively unique case of first-order ferro-ferromagnetic transition originating from an instability of the Fe moment. In addition to large magnetoelastic effects making them potential negative thermal expansion materials, here, we show that Sc0.28Ti0.72Fe2 and related alloys also present sizable magnetocaloric and magnetoresistance effects. Both effects are found substantially larger at the ferro-ferromagnetic transition (Tt1) than near the Curie temperature TC, yet they remain limited in comparison to other classes of giant magnetocaloric materials. We suggest a strategy to improve these properties by bringing the transition at Tt1 close to TC, and test its possible realization by Co or Mn for Fe substitutions. The structural and magnetic phase diagrams of Sc0.28Ti0.72Fe2−xTx alloys with T = Mn or Co are explored. Substitutions for Fe by adjacent Mn or Co elements give rise to a breakdown of the long-range ferromagnetic order, as well as a swift disappearance of finite moment magnetism.